Unbuilt masterworks of the 21st century : inspirational architecture for the digital age - Jones, Will (Thames & Hudson, 2009)
"What happens to the projects that are produced for international competitions when they don't win? Or the grand plans for which hundreds of thousands of dollars or euros are spent in research and development but which are never built? Or the proposals for speculative builders who can't, in the end, raise the money? Or the buildings commissioned by governments which are too visionary to be constructed? A single image might appear in professional journals, but most of the plans will disappear, never to be seen again." "This book features one hundred of the best unbuilt projects proposed since the turn of the millennium by some of the world's greatest contemporary architects, including Norman Foster, Rem Koolhaas/OMA, Foreign Office Architects, Diller Scofidio + Renfro, and Zaha Hadid, as well as rising stars such as Jurgen Mayer H Architects and Asymptote." "Arranged in sections according to function - entertainment spaces, museums, urban plans, education, habitation - the projects are presented in detail through texts that consider the importance of the designs and assess why they weren't built, along with renderings and plans. Many of the more than 600 illustrations have not been seen outside the practices themselves."--BOOK JACKET.